Rethinking Gendered Violence Through Critical Feminist Community-Engaged Research - Colpitts, Emily M.; Crosby, Alison (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
This article analyzes how the conceptualization of gendered violence shapes responses and possibilities for redress in two very different community-engaged research contexts and projects. The first case study examines how Canadian universities enact sexual violence policies from the perspective of student activists and other stakeholders to understand the struggle over the power to define violence and shape institutional responses. The second case study is a participatory action research project that explores how transnational feminist and human rights regimes shape, inform, and often occlude or over-determine the struggles for redress by Indigenous women survivors of wartime sexual violence in Guatemala. In both contexts, we identify the persistent circulation of a particular ‘violence against women’ paradigm that functions as a universalizing exceptionalist imaginary which excludes more complex and situated understandings of violence while legitimizing certain responses over others. We consider the possibilities of critical community-engaged research as a means of challenging this presumed universalism. We explore the complexities of conducting such research as white scholars located within the neoliberal academy, given how its investment in community engagement serves to mask the implications of academic knowledge production in colonial and imperial projects and positions the university and the researcher as “saviours” of the “community.”